STUDI KARAKTERISTIK PADA BASED-PLATE SISTEM ANGKUR DENGAN DAN TANPA GEOTEXTILE - Irnawaty, Irnawaty (Fakultas Teknik Universitas Khairun, 2023)
Slope stability is a fairly broad field, considering that of the several types of geotechnicalconstruction failures, the largest is slope stability failure. Of the several types of natural disasters that occur in Indonesia, floods and landslides are at the top of the list of victims. The aim of this research is to examine the characteristics of based-plate anchor systems with and without geotextiles. The basic concept of an anchored geosynthetic system is to increase compression in the soil under the geosynthetic by driving the anchor to a certain depth. With additional compression on the soil, soil compaction will occur so that the frictional strength of the soil increases. The research carried out included testing in the laboratory. This research will be carried out at the Soil Mechanics Laboratory of the Civil Engineering Department of Hasanuddin University, Makassar. The sample is disturbed soil originating from the location in front of the Laboratory of the Faculty of Engineering, Hasanuddin University, Makassar, South Sulawesi. The relationship between based-plate geometry and load for a tensile load of 2500 kg and a decrease in soil deformation of 0.18 cm. Based on research conducted with a geotextile distance of 15 cm per layer, it can increase tensile strength and reduce the settlement that occurs. An increase in the anchor tensile load results in an increase in soil deformation.